A bionic micro-electromechanical system piezo-resistive vector hydrophone that suppresses vibration noise. (5th September 2019) - Song, Jinlong; Wang, Renxin; Zhang, Guojun; Shang, Zhenzhen; Zhang, Lansheng; Zhang, Wendong
Abstract: For piezo-resistive sensors have outstanding low-frequency response, micro-electro-mechanical system (MEMS) piezo-resistive vector hydrophones play an important role in low-frequency sound waves measurements. However, their signal-noise ratio can be decreased by vibration noise. The conventional solution is to suspend the hydrophone elastically, which can reduce the influence of vibration with frequencies higher than the natural frequency of the elastic element used for suspension. However, this approach has little effect on reducing low-frequency vibration noise. To overcome this problem, a novel hydrophone structure with a large-volume supporting block is proposed in this study. When the hydrophone is subject to vibration, the actions of the supporting block and cilium on the piezo-resistors counteract each other. Therefore, the proposed hydrophone can effectively reduce output voltages caused by vibration. Mathematical models of this new hydrophone are established to verify the feasibility of the method. Simulations are performed and found to be in accordance with the mathematical models. The experimental results clearly demonstrate that the proposed hydrophone can dramatically reduce vibration noise without reducing sensitivity to sound.